PENGARUH KOMPRES HANGAT REBUSAN AIR SEREI TERHADAP PENURUNAN NYERI RHEUMATOID ARTRITIS PADA LANSIA DI PUSKESMAS DELI TUA TAHUN 2020 - Herri Novita Tarigan (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2020)
ABSTRAK Rheumatoid Arthritis disease is an inflammation disease in the elderly with symptoms of stiffness and pain in the joints. To reduce the pain can be done with Non Pharmacological therapy of granting one of them with a warm compress therapy boiled lemongrass water. Lemongrass (Cymbopogon nardus)has a lot of chemical contect, which containts 0.7 % essential oil with three important components such as citronelal, geraniol (20%), and (66-85%) citronelal. The three components have chemical properties and pharmacological effect, namely spicy. This study aimed to analyze the effect of warm compression of lemongrass stew on the reduction of Rheumatoid Arthritis pain in the elderly in the Puskesmas Deli Tua in 2020.This research is a type was quantitative research by using the design method of one-group pretest-posttets experiments. The populations of this study were all in the elderly aged 60-year-olds suffering from rheumatoid arthritis at the Puskesmas Delitua of 30 people. The sampling technique used is non-probability sampling with purposive sampling type based on inclusion and exclusion criteria obtained by 20 respondents. The instrument in the study is an observation pain scale sheet of the Numeric Ractingscale (NRS). The results of the study obtained based on the Wilcoxon Test, the value obtained p =(0,006) < (0.05), it can be interpreted that H0 rejected H1 is accepted meaning that there is a statistically significant influence between warm compresses of lemongrass water to decreased rheumatoid arthritis pain in the elderly in Puskesmas Deli Tua. Compress lemongrass water can be used as one of the alternatives to reduce the intensity of pain of elderly people suffering from rheumatoid arthritis.